Bertrand curves of AW(k)-type in Lorentzian space - Kulahci, Mihriban; Ergut, Mahmut (Pergamon-Elsevier Science Ltd, 2009)
In this study, firstly, we give curvature conditions of AW(k)-type (1 <= k <= 3) Curves. Then considering AW(k)-type curves, we investigate Bertrand curves gamma : I -> L-3 with kappa(1)(s) not equal 0 and kappa(2)(s) not equal 0. We show that there are Bertrand curves of AW(1)-type and AW(3)-type. Moreover, We Study weak AW(2)-type and AW(3)-type conical geodesic curves in L-3. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: AW(k)-type curve; Frenet curvatures; Bertrand curves; Conical geodesic curve